ĐÁNH GIÁ TRẠNG THÁI CHỨC NĂNG CƠ THỂ CỦA THỦY THỦ TÀU NGẦM - Hoàng, Văn Huấn; Bùi, Thị Hương; Nguyễn, Hồng Quang; Trần, Thị Nhài (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF THE BODY FUNCTIONAL STATUS OF SUBMARINERS The body functional status of sixty submariners was assessed by functional neurological and cardiovascular system using the program-apparatus complex Ritm-MET (Moscow, Russia). The evaluations of the body functional state include analysis of heart rate variability registered for 2,5 minutes and sensorimotor reflexes. The results showed that most of investigated submariners were in good functional condition (96,7%). However, some latent stress signs of cardiovascular system and imbalance in regulation of cardiovascular functional activity between the sympathetic and parasympathetic nervous system appeared in some submariners. 3,3% of submariners did “not meet” to professional work because of cardiovascular functional disorders (higher blood pressure and decrease in heart rate variability) and the unsatisfactory passage of psychophysiological tests by individuals.